PENGARUH KEPUASAN KONSUMEN DAN KEPERCAYAAN MEREK PADA NIAT BERKUNJUNG KEMBALI HOTEL DI YOGYAKARTA - RR. Siti Muslikhah; Yuni Astuti; Mahyuddin Mahyuddin (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
This study aimed to examine the effect of customer satisfaction on revisit intention hotel in Yogyakarta, either directly or through the mediation of brand trust. Respondents in this study is that stayed in one-star hotels in Yogyakarta. To test the hypothesis quantitatively, the data obtained through a survey of 106 respondents. Sampling method nonprobability sampling with purposive sampling method. Validity testing performed by Confirmatory Factor Analysis (CFA) while reliability testing performed by the item to total correlation and Cronbach's alpha. Meanwhile, to test the effect among variables used hierarchical regression analysis and analysis of mediation Baron and Kenny (1986). Results from this study is that customer satisfaction significant effect on brand trust, brand trust a significant effect on revisit intention. This study also proved that customer satisfaction significant influence on purchase intention of re-either directly or indirectly, that is mediated confidence in the brand. The role of mediation is partially. Keywords: consumer satisfaction, brand trust, repurchase/revisit intention, mediation.